Dealing with the gray zones in the management of gastric cancer: The consensus statement of the İstanbul Group - Aytaç, Erman; Aslan, Fatih; Çicek, Bahattin; Erdamar, Sibel; Gürses, Bengi; Güven, Koray; Falay, Okan; Karahasanoğlu, Tayfun; Selçukbiricik, Fatih; Selek, Uğur; et al. (Turkish Journal of Gastroenterology, 2019)
Abstract The geographical location and differences in tumor biology significantly change the management of gastric cancer. The prevalence of gastric cancer ranks fifth and sixth among men and women, respectively, in Turkey. The international guidelines from the Eastern and Western countries fail to manage a considerable amount of inconclusive issues in the management of gastric cancer. The uncertainties lead to significant heterogeneities in clinical practice, lack of homogeneous data collection, and subsequently, diverse outcomes. The physicians who are professionally involved in the management of gastric cancer at two institutions in Istanbul, Turkey, organized a consensus meeting to address current problems and plan feasible, logical, measurable, and collective solutions in their clinical practice for this challenging disease. The evidence-based data and current guidelines were reviewed. The gray zones in the management of gastric cancer were determined in the first session of this consensus meeting. The second session was constructed to discuss, vote, and ratify the ultimate decisions. The identification of the T stage, the esophagogastric area, imaging algorithm for proper staging and follow-up, timing and patient selection for neoadjuvant treatment, and management of advanced and metastatic disease have been accepted as the major issues in the management of gastric cancer. The recommendations are presented with the percentage of supporting votes in the results section with related data. Cite this article as: Aytaç E, Aslan F, Çiçek B, et al. Dealing with the gray zones in the management of gastric cancer: The consensus statement of the İstanbul Group. Turk J Gastroenterol 2019; 30(7): 584-98.